2006
DOI: 10.1002/ejic.200500641
|View full text |Cite
|
Sign up to set email alerts
|

Chloro, Alkyl and Aryl Complexes of Rare Earth Metals Supported by Bulky Tetrasubstituted Guanidinate Ligands

Abstract: The reactions of anhydrous LnCl 3 (Ln = Y, Nd, Sm, Lu) with two equiv. of sodium N, NЈ-dicyclohexyl-NЈЈ-bis(trimethylsilyl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 53 publications
3
35
0
2
Order By: Relevance
“…These features are consistent with the symmetry observed in solution by NMR spectroscopy. The Y À O bond length in 1 a of 2.021(2) compares well with the value of 2.005 (10) found for terminal YÀO distances in the six-coordinate yttrium complex [{YCpA C H T U N G T R E N N U N G (m-OCMe 3 )A C H T U N G T R E N N U N G (OCMe 3 )} 2 ] (Cp = cyclopentadienyl). [11] A single-crystal X-ray diffraction study for the lutetium analogue 4 a revealed its structural similarity to 1 a (see Supporting Information; Figure S1).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…These features are consistent with the symmetry observed in solution by NMR spectroscopy. The Y À O bond length in 1 a of 2.021(2) compares well with the value of 2.005 (10) found for terminal YÀO distances in the six-coordinate yttrium complex [{YCpA C H T U N G T R E N N U N G (m-OCMe 3 )A C H T U N G T R E N N U N G (OCMe 3 )} 2 ] (Cp = cyclopentadienyl). [11] A single-crystal X-ray diffraction study for the lutetium analogue 4 a revealed its structural similarity to 1 a (see Supporting Information; Figure S1).…”
Section: Resultssupporting
confidence: 54%
“…The Y À N bond lengths in 1 a are very similar (2.325(3)-2.374(2) ) and are comparable to those reported for related bis(guanidinate)-yttrium complexes. [10] The NÀC bond lengths in the guanidinate ligands differ only slightly from each other (1.328(4)-1.335(4) ), reflecting electron delocalization within the anionic NCN units. These features are consistent with the symmetry observed in solution by NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Several examples of alkyl complexes of rare-earth metals supported by guanidinate ligands were published recently. [31][32][33][34] We employed the advantages of the [(Me 3 Si) 2 …”
Section: Introductionmentioning
confidence: 99%
“…Richeson 等于 1998 年首次报道了胍基稀 土氯化物的合成 [172] , 之后又有多篇文献报道 [173,174] [175] 或者中性二聚体产物(图 29) [176,177] . 当 配体位阻较大时, 生成中性单核氯化物 [178] .…”
Section: 基于含氮配体的稀土金属有机配合物unclassified
“…178,185,186] , 这 些 配 合物在室温下不稳定, 但可以用于原位制备氢化物 [185] . 在 TMEDA 的存在下, 胍基稀土氯化物与 MeLi 在己烷 中反应生成热稳定性较好的盐型配合物 [175,177,187] .…”
Section: β-二亚胺稀土金属有机配合物 β-二亚胺是最为重要的双齿配体unclassified